Integrated Design in Load Carrying and Energy Absorption of Composite Tube - Hu, Hanjie; Du, Bing; Jiang, Wenkai; Zheng, Changqi; Zhu, Ning; Liu, Jingwei; Chen, Liming (Frontiers in Materials, 2022)
In this paper, a type of tube with an open-hole AL alloy tube nested outside the CFRP tube is designed and fabricated, and the energy absorbing characteristics and failure mechanism under quasi-static axial compression are discussed. It is found that the summing tube composed of two single tubes has less energy absorption than the hybrid tube. Numerical simulation and theoretical model are used to evaluate the influence of the hybrid tube in terms of cost and weight, and it is found that under the same energy absorption, the hybrid tube has a weight reduction of 39.2% compared to the open-hole AL tube, 25.7% of the cost of CFRP tube. This hybrid structure has potential as the load carrying and energy absorption tube.